Factors Causing Differences In The Financial Reporting Practices In Selected South Pacific Countries In The Post-Convergence Period - Chand, Parmod; Patel, Chris; Day, Ronald (Asian Academy of Management (AAM), 2008)
The international accounting literature pays much attention to the clustering of national accounting systems of various countries based on similar financial reporting characteristics. In this paper, we argue that the existing models that cluster countries are substantially incomplete and misleading due to the recent convergence efforts that have taken place. We identify the factors that may be causing differences in both the de jure and de facto aspects of comparability in financial reporting across countries in the postconvergence period. Using four countries from the South Pacific region (Australia, New Zealand, Papua New Guinea and Fiji), we identify three dominant factors that still act as constraints in accounting convergence. These include: (1) the nature of business ownership and the financial system, (2) culture, and (3) the level of accounting education and the experience of professional accountants in each of the different countries. We argue that national and international regulators need to work towards reducing these remaining differences across countries to achieve the objectives of accounting convergence.